Autologous Genetically Enriched Leucoconcentrate in the Preventive and Acute Phases of Stroke Treatment in a Mini-Pig Model - Zufar Safiullov; Andrei Izmailov; Mikhail Sokolov; Vage Markosyan; Grayr Kundakchan; Ravil Garifulin; Maksim Shmarov; Boris Naroditsky; Denis Logunov; Rustem Islamov (MDPI AG, 2022)
The natural limitations of regeneration in the CNS are major problems for the treatment of neurological disorders, including ischaemic brain strokes. Among the approaches being actively developed to inhibit post-ischaemic negative consequences is the delivery of therapeutic genes encoding neuroprotective molecules to the brain. Unfortunately, there are currently no proven and available medicines that contain recombinant human genes for the treatment of ischaemic cerebral stroke. Of particular interest is the development of treatments for patients at risk of ischaemic stroke. In the present study, we propose a proof of concept for the use of an autologous, genetically enriched leucoconcentrate temporally secreting recombinant vascular endothelial growth factor (VEGF), glial-cell-line-derived neurotrophic factor (GDNF) and the neural cell adhesion molecule (NCAM) for the treatment of stroke. In a mini-pig ischaemic stroke model, genetically enriched leucoconcentrate was infused 4 h after surgery (gene therapy in acute phase) or 2 days before stroke modelling (preventive gene therapy). On day 21, after the stroke modelling, the post-ischaemic brain recovery was examined by morphologic and immunofluorescence analysis. The benefits of treating a stroke with genetically enriched leucoconcentrate both for preventive purposes and in the acute phase were confirmed by an improved performance in behavioural tests, higher preservation of brain tissue and positive post-ischaemic brain remodelling in the peri-infarct area. These results suggest that the employment of autologous leucocytes enabling the temporary production of the recombinant therapeutic molecules to correct the pathological process in the CNS may be one of the breakthrough approaches in gene therapy.